The ways to improve the system of control over labour and equipment safety at the current stage of economic development - Yu. V. Baranov; D. Yu. Filippov (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the state of the organization of state control at the present stage of economic development in the field of ensuring labor and equipment safety. An analysis of inspections in this area showed a decrease in their number by federal inspections in order to reduce the burden on business. When studying the regulatory framework of the Russian Federation on labor and equipment safety, as well as examining statistical data regarding the state of labor protection and equipment safety in the Russian Federation, a conclusion was made about the lack of control in this area. In this regard, the organizational development of public control is proposed.